Linguistic, scriptural, and semantic processes of the term quniraya - Cisneros Ayala, Claudia (2024)
This essay aims to identify the scriptural and semantic variations and linguistic processes in the morphosyntax of the terms quniraya, kumirraya, kuniraya, quñiraya, quniraya, -iraya. Corpora concerning quniraya were identified in Hispanic chronicles, 16th-century colonial dictionaries, and both historical and contemporary documents, which were then organized and compared to examine the writing, the processes that occurred within the word, and ultimately to determine its semantics. For this purpose, a textual record was utilized. After identification, the processes were analyzed and explained to verify phenomena such as syncope, fricativization, velarization, palatalization, suppression, apheresis, and pronunciation, among others. From these explanations, it can be concluded that these processes led to the loss of the word's sememe, but reconstructing the morphosyntactic structure and the term's script provided greater clarity in meaning.